Surgical Removal of Air Rifle Projectiles in Long-Tailed Macaques (Macaca fascicularis) in the Ubud Monkey Forest - Sewoyo, Palagan Senopati; Wirata, I Wayan; Gorda, I Wayan; Wardhita, Anak Agung Gde Jaya; Bebas, I Wayan; Soma, I Gede; Putra, I Gusti Agung Arta; Wandia, I Nengah; Brotcorne, Fany (Universitas Airlangga, 2025)
Background: Long-tailed macaques (Macaca fascicularis) frequently share their habitat with humans, leading to conflicts, especially when habitat disturbances force them to exploit human food sources. In response, humans sometimes use air rifles to deter these animals. Preventive measures such as sterilization programs, habitat restoration, and public education about responsible interactions with macaques are essential to reduce the occurrence of such incidents and promote coexistence. Purpose: This report describes the anesthesia and surgical management of gunshot wounds in long-tailed macaques. Case(s): Two adult free-ranging male long-tailed macaques in the Ubud Monkey Forest, Bali, Indonesia, were presented with gunshot wounds on the inguinal region and right caudal pelvic area, respectively. These macaques were captured and anesthetized for a scheduled vasectomy. A detailed clinical examination indicated that the projectiles were lodged in the subcutaneous tissue. Based on their shape and size, the projectiles were suspected to be 0.177 caliber (4.5 mm) air rifle pellets. Case Management: Surgical removal was performed to extract the air rifle pellets. Preoperatively, the macaques received amoxicillin (15 mg/kg BW, IM), ketorolac (2.5 mg/kg BW, IM), and Visine® eye lubricant. Propofol was used for anesthetic maintenance (1 mg/kg BW, IV). Following pellet removal, the wound was sutured with monofilament absorbable poliglecaprone 25, and the planned vasectomy was conducted using the bilateral incision method. Postoperatively, the macaques were administered atipamezole (0.02 mg/kg BW, IM) for anesthesia reversal, placed in recovery cages in lateral recumbency, and closely monitored. Conclusion: Once the macaques showed clear signs of recovery from anesthesia, they were transported back to the capture site and released into their original group.